2024
DOI: 10.1371/journal.pntd.0011872
|View full text |Cite
|
Sign up to set email alerts
|

A novel Trichinella spiralis serine proteinase disrupted gut epithelial barrier and mediated larval invasion through binding to RACK1 and activating MAPK/ERK1/2 pathway

Yan Yan Song,
Xin Zhuo Zhang,
Bo Ning Wang
et al.

Abstract: Background Gut epithelium is the first natural barrier against Trichinella spiralis larval invasion, but the mechanism by which larval penetration of gut epithelium is not completely elucidated. Previous studies showed that proteases secreted by T. spiralis intestinal infective larvae (IIL) degraded tight junctions (TJs) proteins of gut epithelium and mediated larval invasion. A new T. spiralis serine proteinase (TsSPc) was identified in the IIL surface proteins and ES proteins, rTsSPc bound to the intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, RACK1 proteins have been identified as multifunctional proteins with high biological conservation across different species [ 42 , 43 , 44 ]. Further investigation revealed the presence of seven repeated WD40 structures in the protein, forming seven beta propeller structures that serve as central channels for protein binding in both prokaryotes and eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, RACK1 proteins have been identified as multifunctional proteins with high biological conservation across different species [ 42 , 43 , 44 ]. Further investigation revealed the presence of seven repeated WD40 structures in the protein, forming seven beta propeller structures that serve as central channels for protein binding in both prokaryotes and eukaryotes.…”
Section: Discussionmentioning
confidence: 99%